DENTIST IN LEADERSHIP POSITION AS CHIEF EXECUTIVE OFFICER OF A LEADING TERTIARY HEALTH INSTITUTION IN NIGERIA. - Onatolu Odukoya (Nigerian Dental Association, 2023)
This article was written with the aim of sharing the experience of the author as a dentist who served as a Chief Medical Director of Lagos University Teaching Hospital for a total of 8 years from 1998 to 2006. The authors discussed circumstances that led to his emergence as Chief Medical Director, the challenges he faced on the job, the significant achievements he made and his final exit from the job. It is hoped that every dentist that reads this article will have confidence to aspire for the job. The author concluded that on the basis of his experience, there should be increased participation of the private sector in funding and managing tertiary health institutions in Nigeria.